HERDEIROS DE UMA TRADIÇÃO: UMA INVESTIGAÇÃO DOS FUNDAMENTOS TEOLÓGICO- IDEOLÓGICOS DO CONSERVADORISMO METODISTA NA CRISE DA DÉCADA DE SESSENTA - Schmidt, Daniel Augusto (2008)
This work studies the crisis experienced by the Methodist Church of Brazil in the second half of the 1960's. Influenced by the political environment of the military dictatorship, Brazilian Methodism was a space of collision between liberal and conservative groups of the denomination. The principle space of this collision was the School of Theology and the II Extraordinary General Council, in 1968, as well as a series of events that followed during the years 1969 and 1970. The research raises questions regarding the theological and ideological foundations that provided the bases for the attitudes of the conservative groups of Methodism in this conflict, which is an aspect rarely considered by historical studies regarding the theme. The principle suspicion is that the conservative positions originated from a centuries old tradition, brought by North American missionaries during the implantation of Protestantism in Brazil. This tradition was transformed into an Ethos of Brazilian Protestantism between the end of the XIX and the middle of the XX century. The conservative position was configured, as such, in reaction to the Ethos threatened by new actors in the religious field and by the demands of a society in conflict.(AU)